THE AUDIT COMMITTEES AND EARNINGS QUALITY IN EUROPE - Marques, G.; Pais, C. (41th annual congress European Accounting Association, 2018)
The attention and concern regarding corporate governance structures’ effectiveness, particularly concerning audit committees’ effectiveness, in safeguarding the interests of investors has been growing. Prior literature has focused on the analysis of some characteristics of audit committees in improving earnings quality. Notwithstanding the various studies addressing this analysis the results are mixed. This study focuses on the analysis of the relation between the independence, expertise and number of audit committee members and the number of meetings held and earnings quality for European companies. Earnings quality is proxied by a modified Jones (1991) model. The results show evidence of a positive relation between the proportion of independent members of the audit committee, the number of members and the number of meetings held, and earnings quality. However the study does not provide any evidence of a positive relation between the existence of more than one expert member and earnings quality. Our conclusions suggest that more independent, bigger and active are the audit committees more effective are in constraining earning management practices. This study contributes to previous literature by studying European companies, measuring some characteristics of the audit committee differently and analysing whether the level of investor protection influences the relation between the characteristics and earnings quality.